The Role of Bedtime Storytelling for Optimizing Early Childhood Communication Skills - Astri Dwi Andriani (PT FORMOSA CENDEKIA GLOBAL, 2022)
In the modern era, storytelling is rarely done. A survey conducted by Disney in England proved that only a third of parents in England still have time to read fairy tales. Even though there are many benefits from storytelling, from developing imagination to honing communication skills. This research uses library research which includes: systematic identification, analysis of documents containing information related to the study problem. The technique used is content analysis or content review. The results of the study show that children's companions must pay attention to reading materials according to the age range as an effort to optimize children's communication skills: 1) Children aged 0-2 years, choose fairy tales about real objects; 2) Children aged 2-4 years choose fairy tales by role playing; 3) Children aged 4-7 years can be introduced to more complex fairy tales.